Barracks and fortresses. A comparative review of the military architecture of Hungary and the Russian Far East - Ivanova Alina P.; Csanádi Gabor; Stelmakova Tatiana O. (Архитектон, 2023)
The article, written within the framework of the Russian-Hungarian project “The Architectural Image of the Motherland: Budapest-Petersburg-Harbin”, is devoted to the architecture of fortifications and garrisons. In the first, Hungarian, part, the role of fortress architecture in the formation of national identity and (using two examples) the architecture of barracks are reviewed. The main goal of the second, Far Eastern Turkestan, part is to identify the role of garrison towns as a “civilization matrix” that transmits the culture of the metropolis to the outskirts of the empire. In the third part, the topic of fortresses and military settlements is addressed using the example of Port Arthur and the project of “soldiers’ settlements” along the Chinese Eastern Railway.